Rationale and protocol of a double-blind, randomized, placebo-controlled trial to test the efficacy, safety, and tolerability of dimethyl fumarate in Friedreich Ataxia (DMF-FA-201) - Pane, Chiara; Marra, Alberto Maria; Aliberti, Ludovica; Campanile, Mario; Coscetta, Federica; Crisci, Giulia; D'Assante, Roberta; Marsili, Angela; Puorro, Giorgia; Salzano, Andrea; Cittadini, Antonio; Saccà, Francesco (Frontiers in Neuroscience, 2023)
Introduction: Friedreich ataxia (FRDA) is an autosomal recessive neurodegenerative disorder causing gait and limb ataxia, dysarthria, impaired vibratory sense, with cardiomyopathy being the predominant cause of death. There is no approved therapy, which results in the use of symptomatic treatments, and in the chronic support of physiotherapy. Dimethyl fumarate (DMF) is a fumaric acid ester used for the treatment of psoriasis and Multiple Sclerosis (MS).It induces Nrf2 in vitro and in vivo, and it increases frataxin in FRDA patient lymphoblasts, in mouse models, and in MS treated patients.Methods: aim of our study is to investigate if DMF can increase the expression of the FXN gene and frataxin protein and ameliorate in-vivo detectable measures of mitochondrial dysfunction in FRDA. The study is composed of a screening visit and two sequential phases of identical length of 12 weeks each: a core phase and an extension phase. During the first phase (core), patients will be randomly assigned to either DMF or placebo in a 1:1 ratio. During the first week, patients will receive a total daily dose of 240 mg of DMF or placebo, from the second week of treatment, the dose will be increased to two 120 mg tablets BID for a total daily dose of 480 mg. During the second phase (extension), all patients will be treated with DMF.EudraCT number 2021-006274-23.Endpoints: Primary endpoint will be a change in FXN gene expression level after 12 weeks of treatment. Secondary Endpoints will be: frataxin protein level, cardiopulmonary exercise test outputs, echocardiographic measures, Nrf2 pathway and mitochondrial biogenesis gene expression, safety, clinical scales, and quality of life scales.Conclusions: this is the first study aimed at exploring the ability of DMF, an already available treatment for MS and psoriasis, to correct the biological deficits of FRDA and potentially improve mitochondrial respiration in-vivo.